Determinants of productivity in food industries of Iran - Afrooz, Ahmad; Abdul Rahim, Khalid; Edalati, Ali (Elixir, 2011)
Considering to importance of Food Industries related to generate employment, more so than many other manufacturing sector and also it’s vital role in Iran’s economy. This paper examines the determinants of labour productivity in food industries of Iran over the 1995-2006 period. The study applied the Cobb–Douglas production function of industry. The results showed that total factor productivity is 17.8 percent. The determinants like education, skilled, specialist, capital per worker and wages have affected on productivity’s differences in Iranian food industries. The most important factor was employee’s specialization in this industry.